LOCAL SELF-GOVERNMENT IN ENSURING THE SUSTAINABLE DEVELOPMENT IN THE COUNTRY - Myhovych Т.М. (The actual problems of regional economy development, 2019)
The article describes the essence of the concept the “sustainable development”, which aims to integrate the goals of high quality life, health and well-being with social justice and to meet the needs of the present generation, without sacrificing future opportunities. The influence of the decentralization process on the ability of local self-government to provide quality services to the population has been determined. The successes of decentralization and progress in the formation of capable individual territories were noted. The positive moment of decentralization is the formation of local identity by the community, which ensures the rational use of available resources and increases the activity of local communities. A number of problems have been formulated that arise in the process of implementing the redistribution reform between the government levels and resources, namely the excessive financial system decentralization complicates the implementation by the state of such a function as the stabilization and redistribution of income. It was noted that a holistic vision of the expected changes from the decentralization reform was laid down in the Concept of the reforming local self-government and territorial organization government in Ukraine. The author reflects the role of local self-government in ensuring the sustainable development in the country. The components of local finance have been identified as the basis for territorial self-sufficiency. Regulating the regional development in Ukraine is accomplished through a series of tools that show varying degrees and effectiveness over time. The relevance of the using grants as a source for ensuring the effective functioning of local self-government has been clarified. Several EU grant programs have been identified to fund regional development projects, in particular in the field of transport, to assist social and economic transformation, education and innovation.